Kondisi pasar Indonesia dalam isu inflasi nasional dan geopolitik global - Luntungan, Deilamy (Yayasan Widyantara Nawasena Raharja, 2024)
In early 2022, changes in the inflation rate accompanied by global geopolitical issues became crucial information for the Indonesian capital market. At that time, inflation conditions in Indonesia began to creep up to reach a point of around 2%. This study aims to examine the market return performance of the LQ45 Index in the context of changes in the inflation rate and global geopolitical issues. Observations are carried out in 2 sub-periods: (1) 6 October 2021 to 30 December 2021 or the period with low inflation; and (2) January 3 2022 to March 31 2022 or a period with a high inflation rate. The findings of this study show that the highest market returns with low risk are in periods of high inflation and accompanied by global geopolitical issues. This period also produces a better risk-return trade-off. Other findings indicate that the market in both periods did not produce extraordinary returns even though it was in a weak form of inefficiency. Changes in the inflation rate accompanied by global geopolitical issues did not significantly change market returns.